(3x+18)(3x+18)=36

Simple and best practice solution for (3x+18)(3x+18)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+18)(3x+18)=36 equation:


Simplifying
(3x + 18)(3x + 18) = 36

Reorder the terms:
(18 + 3x)(3x + 18) = 36

Reorder the terms:
(18 + 3x)(18 + 3x) = 36

Multiply (18 + 3x) * (18 + 3x)
(18(18 + 3x) + 3x * (18 + 3x)) = 36
((18 * 18 + 3x * 18) + 3x * (18 + 3x)) = 36
((324 + 54x) + 3x * (18 + 3x)) = 36
(324 + 54x + (18 * 3x + 3x * 3x)) = 36
(324 + 54x + (54x + 9x2)) = 36

Combine like terms: 54x + 54x = 108x
(324 + 108x + 9x2) = 36

Solving
324 + 108x + 9x2 = 36

Solving for variable 'x'.

Reorder the terms:
324 + -36 + 108x + 9x2 = 36 + -36

Combine like terms: 324 + -36 = 288
288 + 108x + 9x2 = 36 + -36

Combine like terms: 36 + -36 = 0
288 + 108x + 9x2 = 0

Factor out the Greatest Common Factor (GCF), '9'.
9(32 + 12x + x2) = 0

Factor a trinomial.
9((8 + x)(4 + x)) = 0

Ignore the factor 9.

Subproblem 1

Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4

Solution

x = {-8, -4}

See similar equations:

| 4-2a=m | | 3x^2-12x+2x-8= | | 8x-(4x+6)=10 | | (3n+2)=0 | | 2(7x-1)=29 | | x^2+14=9x | | -3x+5=-3 | | -75y+.25=.50 | | 4x+2=21 | | (2a-4)=m | | -q+5=10 | | p+.30p=666666667 | | K-3k+3=11 | | 9y^2-y= | | -y-3=8 | | 7d-13=17+3d | | 3(x+1)-7=20 | | 4x^2+7x=0 | | -x+100=100 | | 7(v+17)=6v | | -m+2=1 | | 3a+(2-2a)=a+2 | | -7=-c-29 | | x^2-9x+7=0 | | -5t^2+60t= | | -b+6=-16 | | 4(z-5)+2=z+3 | | 6x^2-22xy-12Y^2=0 | | 16x^5y^3+36x^3y^5= | | -(-3x+w)-4(2w+4x)= | | (3x+4)-(x+3)=3x+2+5x | | 8x+6=-9 |

Equations solver categories